Оптимізація порядку переміщення контейнерів під час обробки потягів на перевантажувальній станції - Калайда, Н. С. (ХНУРЕ, 2020)
During the transportation of goods by rail, there are problems of processing trains and performing railway terminal operations at the transshipment yard (TSY) of the railway transshipment station. It is necessary to create a mathematical model of these processes and optimize them for the rational use of human and material resources at the transshipment yard. This paper is an attempt to create mathematical model to identify of optimal sequence of the gantry crane movement at the transshipment yard.